ICTV Virus Taxonomy Profile: Parvoviridae - Cotmore, Susan F.; Agbandje-McKenna, Mavis; Canuti, Marta; Chiorini, John A.; Eis-Hubinger, Anna-Maria; Hughes, Joseph; Mietzsch, Mario; Modha, Sejal; Ogliastro, Mylène; Pénzes, Judit J.; Pintel, David J.; Qiu, Jianming; et al. (Journal of general virology, 2019)
Members of the family Parvoviridae are small, resilient, non-enveloped viruses with linear, single-stranded DNA genomes of 4–6 kb. Viruses in two subfamilies, the Parvovirinae and Densovirinae , are distinguished primarily by their respective ability to infect vertebrates (including humans) versus invertebrates. Being genetically limited, most parvoviruses require actively dividing host cells and are host and/or tissue specific. Some cause diseases, which range from subclinical to lethal. A few require co-infection with helper viruses from other families. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the Parvoviridae , which is available at www.ictv.global/report/parvoviridae .